Rasio Tepung Sagu (Metroxylon sagu Rottb) dan Pati Ganyong (Canna discolor) Terhadap Karakteristik Pempek Ikan Rucah - Eka Lidiasari; Irmayanta Tarigan; Basuni Hamzah; Tamaria Panggabean; Parwiyanti Parwiyanti (Jurnal FishtecH, 2023)
The objective of this research was to determine the effect of sago flour and canna flour additions on the characteristics of trash fish pempek. The research was conducted at Agricultural Product Chemical Laboratory of Agricultural Technology Faculty of Agriculture, Sriwijaya University. The research used a Non Factorial Completely Randomized Design (CRD) with the treatment of flour formulation that was sago flour and canna flour as much as six treatments and each treatments was repeated three times. The observed parameters were texture, moisture content, protein content, crude fiber content and organoleptic (flavor, taste, and texture). The result showed that the subtition of wheat flour with sago flour and canna flour had significant effects on texture,and organolepic (flavor,taste, and texture). Pempek trash fish with a ratio of 80% sago flour and 20% canna flour was the best treatment according to sensory evaluation (flavor, texture,and taste) which was categorized as liked by panelists.